External and firm factors effecting takaful industry performance in Malaysia - Raihan, Siti (2025)
This study was conducted to assess the performance of Islamic insurance companies in Malaysia. This study attempts to test internal factors, namely liquidity, return on equity, leverage, company size, underwriting risk, investment and external factors; gross domestic product and inflation on the performance of Islamic insurance companies referring to return on assets. This study involved all Takaful operators in Malaysia for thirteen years, namely from 2011 to 2023. It was reported that 15 Islamic insurance companies registered with Bank Negara Malaysia (BNM) were included in this study. Secondary data collected in this study came from the annual financial reports (balance sheets and income statements) of Islamic insurance companies; and from the World Bank Indicators for gross domestic product per capita and consumer price index. The method used in this study is Multiple regression analysis. This study found that the performance of Islamic insurance companies is determined by leverage, size of firm, GDP, and Inflation Rate. However, this study found that the factors of liquidity, equity return, underwriting risk, and investment did not have a significant effect on the performance of Islamic insurance companies in Malaysia. The implications of this study can be a guide for investors in making investment decisions, customers in choosing profitable Takaful policies, and the government in developing the Takaful industry in Malaysia